Costs, Trends, and Related Factors in Treating Lung Cancer Patients in 67 Hospitals in Guangxi, China. (28th May 2017) - Zhou, Li-Fang; Zhang, Mao-Xin; Kong, Ling-Qian; Lyman, Gary H.; Wang, Ke; Lu, Wei; Feng, Qi-Ming; Wei, Bo; Zhao, Lue Ping
ABSTRACT: Lung cancer is a common disease with high mortality in China. Recent economic advances have led to improved medical capabilities, while costs associated with treating this disease have increased. Such change contributes to a commonly held belief that healthcare costs are out of control. However, few studies have examined this issue. Here, we use 34, 678 hospitalization summary reports from 67 Guangxi hospitals (period 2013–2016) to document costs, temporal trends, and associated factors. Findings from this study are surprising in that they debunk the myth of uncontrolled healthcare costs. In addition, results and experiences from Guangxi are informative for other comparable regions.